2018
DOI: 10.3390/v10030103
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interactions Between Bacteriophage phiIPLA-RODI and Four Chemical Disinfectants for the Elimination of Staphylococcus aureus Contamination

Abstract: Bacteriophages are currently considered as a promising alternative to antibiotics and disinfectants. However, the use of phages in different clinical and industrial settings will involve their exposure to other disinfectants. As a result, the outcome of the phage treatment will depend on two aspects derived from such interactions. On the one hand, the susceptibility of the phage to disinfectants at the concentrations used for disinfection and at lower residual concentrations needs to be determined. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 19 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…The E. coli phage on the other hand was chosen taking advantage of its known morphologic and genomic characteristics, and also due to its known survival on two polyflora honeys (Oliveira et al, 2017 ) during the first 6 h. In this work, chestnut honey partially or completely destroyed both phages after 24 h of exposure resulting in phage concentrations below the limit of detection. The main characteristics of honey that seem to cause loss in phage viability are its low pH (between 3.2 and 4.5), high sugar content (about 80%) that can cause an osmotic shock, possible presence of proteases, and the slow release of hydrogen peroxide when dissolved in water (about 1 mmol.L −1 ) (Rossano et al, 2012 ; Agún et al, 2018 ). Nevertheless, this late destruction of phage particles, only at 24 h, grants them capacity to complete several infection cycles before destruction since both phages have relatively short latent and burst periods (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli phage on the other hand was chosen taking advantage of its known morphologic and genomic characteristics, and also due to its known survival on two polyflora honeys (Oliveira et al, 2017 ) during the first 6 h. In this work, chestnut honey partially or completely destroyed both phages after 24 h of exposure resulting in phage concentrations below the limit of detection. The main characteristics of honey that seem to cause loss in phage viability are its low pH (between 3.2 and 4.5), high sugar content (about 80%) that can cause an osmotic shock, possible presence of proteases, and the slow release of hydrogen peroxide when dissolved in water (about 1 mmol.L −1 ) (Rossano et al, 2012 ; Agún et al, 2018 ). Nevertheless, this late destruction of phage particles, only at 24 h, grants them capacity to complete several infection cycles before destruction since both phages have relatively short latent and burst periods (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the outcome of the phage treatment might depend on the susceptibility of the phage to the biocides as well as the existence of synergistic or antagonistic interactions between phages and these chemical agents. For instance, Agun et al (2018) determined that benzalkonium chloride would be the most adequate disinfectant to apply in combination with the staphylococcal phage phiIPLA-RODI, as this phage can survive at the concentrations of the biocide generally used to inhibit bacterial growth and no antagonism was observed between both antimicrobials.…”
Section: Applications Of Bacteriophages Along the Dairy Chainmentioning
confidence: 99%
“…This includes active substances such as potassium peroxymonosulfate, ethoxylated nonylphenol, Triclosan, chlorhexidine diacetate, Quaternary Ammonium Compounds (QACs) such as benzalkonium chloride or ionic liquids, Chloramine-T and monochloramine, which have drawn the interest of research groups [41,169,171,173,174,175,176,177,178]. More information regarding the regulation of these substances is included in the supplemental material of this review (see Table S4).…”
Section: Legal Regulation Of Disinfectants Currently Used In Food mentioning
confidence: 99%
“…Hosseinidoust et al [36] concluded that a combined use with antibiotics or disinfectants could be a promising strategy to minimize the risk of development of phage-resistant mutants. As a result, different studies have already investigated the influence of antibiotics and disinfectants on the bacterial-phage-system, whereas synergistic effects of antibiotics [39,40] as well as antagonistic effects of disinfectants [41] on this ecosystem were observed. More often, however, the use of phage mixtures and rotations are discussed to avoid or at least limit the development of resistant mutants [30,42].…”
Section: Introduction—advantages and Disadvantages Of Commerciallymentioning
confidence: 99%